Book Review Membrane Technology and Applications 3rd and 4th Edition (Journal of Applied Membrane Science & Technology, 2025)
The book Membrane Technology and Applications by Richard W. Baker has long served as a foundational reference for researchers in the field of membrane technology. It covers a wide range of fundamental concepts and practical applications of membranes in areas such as gas separation, water purification, and pervaporation. This review highlights the key differences between the third and fourth editions of the book. Significant updates and new data introduced in the fourth edition are also discussed. The inclusion of up-to-date technologies aligned with the latest 12 years of development in membrane science provides valuable insights to researchers, ensuring the book remains relevant and reflective of current trends in the field. As membrane technology continues to evolve, the design of treatment systems has become increasingly complex, requiring more advanced configurations and integration with other processes. At the same time, the nature of the chemicals to be treated—ranging from emerging contaminants to high-strength industrial effluents—has also grown more diverse and challenging. This complexity underscores the need for up-to-date knowledge, like that provided in the book, to support researchers in developing effective and innovative membrane solutions.
Keywords: Membrane preparation, gas transport mechanism, membrane application, membrane module, membrane contactors